“Little Glory Will It Bring You To Break My Short Bones“: Dvergar and Dwarfism in Icelandic Medieval Narrative - Bower, Alice (Scandinavian-Canadian Studies / Études scandinaves au Canada, 2026)
This paper explores representations of dvergar (sing. dvergr) in medieval Icelandic narrative sources to ascertain to what extent dvergar were associated with dwarfism and how these links developed over time. The first section of the study focuses on mythological representations of dvergar. In the second section, the analysis turns to Sneglu-Halla þáttr’s Túta, an early example of a human character whose physical description references dvergar. The final section examines the dvergar characters of the legendary sagas (fornaldarsögur) and romance sagas (riddarasögur), which would influence later portrayals of dvergar in Icelandic folklore. The aim of this research is to contribute to further clarification of the historical relationship between dvergar and dwarfism in Icelandic narratives.